2020
DOI: 10.1136/ijgc-2020-001227
|View full text |Cite
|
Sign up to set email alerts
|

Combining novel agents with radiotherapy for gynecologic malignancies: beyond the era of cisplatin

Abstract: Therapeutic strategies combining radiation therapy with novel agents have become an area of intense research focus in oncology and are actively being investigated for a wide range of solid tumors. The mechanism of action of these systemic agents can be stratified into three general categories: (1) enhancement or alteration of the immune system; (2) disruption of DNA damage response mechanisms; and (3) impediment of cellular signaling pathways involving growth, angiogenesis, and hypoxia. Pre-clinical data sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 100 publications
0
17
0
Order By: Relevance
“…There, it is shown that the efficacy of low doses of fractionated RT can be enhanced when delivered in combination with antibodies against PD-1 and PD-L1 [ 87 ]. Currently, there are several ongoing clinical trials in patients with advanced uterine cancers testing monoclonal antibodies against key immune checkpoint inhibitors, such as durvalumab (PD-1), pembrolizumab (PD-1), tremelimumab (CTLA-4) or TSR-042 (PD-1), administrated simultaneously or sequentially to RT [ 88 ].…”
Section: Signaling Pathways and Cellular Processes Modulating Radimentioning
confidence: 99%
“…There, it is shown that the efficacy of low doses of fractionated RT can be enhanced when delivered in combination with antibodies against PD-1 and PD-L1 [ 87 ]. Currently, there are several ongoing clinical trials in patients with advanced uterine cancers testing monoclonal antibodies against key immune checkpoint inhibitors, such as durvalumab (PD-1), pembrolizumab (PD-1), tremelimumab (CTLA-4) or TSR-042 (PD-1), administrated simultaneously or sequentially to RT [ 88 ].…”
Section: Signaling Pathways and Cellular Processes Modulating Radimentioning
confidence: 99%
“…3,4 Surgery followed by chemotherapy is currently the standard therapy for ovarian cancers. 5 Platinum-based drugs (e.g., cisplatin and carboplatin) and paclitaxel are traditional first-line therapies. 6,7 Although ovarian cancer diagnosed in the early stage may be treated successfully, as the disease progresses, most advanced-stage patients develop resistance to first-line drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer is the second most commonly diagnosed cancer in women worldwide, 2 and the mortality rate is worse than other reproductive cancers because of difficulty in early diagnosis 3,4 . Surgery followed by chemotherapy is currently the standard therapy for ovarian cancers 5 . Platinum‐based drugs (e.g., cisplatin and carboplatin) and paclitaxel are traditional first‐line therapies 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Several of the mentioned ongoing clinical trials are supported by rationale that exploits ‘in-field’ tumor–tissue interactions of radiotherapy and various biological agents. Since radiotherapy can cause direct injury to tumor DNA, many of the most promising strategies are directed at perturbation of high-fidelity DNA damage response (DDR) repair 9. Although mechanistically, inhibition of DNA damage response elements and cell-cycle checkpoints appear to have differing levels of individual lethality, their combination with radiotherapy increases the probability of success through sensitization or modality–drug synergy.…”
mentioning
confidence: 99%
“…It is in this latter case that the availability of specific immune checkpoint inhibitors, such as those targeting PD-1/PD-L1, have changed the landscape of systemic therapy for a number of solid tumors, including gynecologic cancer. Lin and colleagues outline these effects and strategies nicely in their review 9. Perhaps one of the most intriguing effects is that related to remote tumor control following localized radiation - termed the ‘abscopal’ (or ab scopal, ‘away from target’) effect.…”
mentioning
confidence: 99%